Multifunctional 3D-printed bioceramic scaffolds: Recent strategies for osteosarcoma treatment - Xingran Liu; Yihao Liu; Lei Qiang; Ya Ren; Yixuan Lin; Han Li; Qiuhan Chen; Shuxin Gao; Xue Yang; Changru Zhang; Minjie Fan; Pengfei Zheng; et al. (Journal of Tissue Engineering, 2023)
Osteosarcoma is the most prevalent bone malignant tumor in children and teenagers. The bone defect, recurrence, and metastasis after surgery severely affect the life quality of patients. Clinically, bone grafts are implanted. Primary bioceramic scaffolds show a monomodal osteogenesis function. With the advances in three-dimensional printing technology and materials science, while maintaining the osteogenesis ability, scaffolds become more patient-specific and obtain additional anti-tumor ability with functional agents being loaded. Anti-tumor therapies include photothermal, magnetothermal, old and novel chemo-, gas, and photodynamic therapy. These strategies kill tumors through novel mechanisms to treat refractory osteosarcoma due to drug resistance, and some have shown the potential to reverse drug resistance and inhibit metastasis. Therefore, multifunctional three-dimensional printed bioceramic scaffolds hold excellent promise for osteosarcoma treatments. To better understand, we review the background of osteosarcoma, primary 3D-printed bioceramic scaffolds, and different therapies and have a prospect for the future.